"Beautiful girl": the culture of miscegenation in the identitarian discourse of Ana Maria Machado - Aparicio García, Isabel (Ondina - Ondine, 2020)
In this article we show the results of the research carried out with a group of 4th grade-students of Primary School about the tale Beautiful girl (2016) written by Ana Maria Machado, published by Ekaré. In the frame of the interpretative paradigm, we have chosen the Chambers’ approach, which has allowed us to obtain the reading responses of both girls and boys. By means of these responses, we have been able to look into their ability to make intertextual connections, as well as to assess the influence that reading literature has in the construction of their (specific) identities. Moreover, we wanted to know if there are significant differences within the responses of girls and boys. Key words: literary reading, reading responses, Chambers’ approach, Ana Maria Machado, "Beautiful girl".